2013
DOI: 10.1093/hmg/ddt437
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomes are enriched in ΔNp73, which promotes oncogenic potential in acceptor cells and correlates with patient survival

Abstract: Tumor-derived exosomes are emerging as local and systemic cell-to-cell mediators of oncogenic information through the horizontal transfer of mRNAs, microRNAs and proteins during tumorigenesis. The exosomal content has been described as biologically active when taken up by the recipient cell. Identifying the specific molecular cargo of exosomes will help to determine their function in specific steps of the tumorigenic process. Here we evaluate whether ΔNp73 is selectively packaged in tumor-derived exosomes, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 24 publications
4
85
1
1
Order By: Relevance
“…The level of circulating exosomes has also been reported to correlate with poor prognosis parameters and shorter survival in colorectal cancer patients [47]. Some exosomal proteins or miRNAs have shown prognostic value in cancer patients, for example, exosomal ΔNp73 and exosomal miRNA in colon cancer, breast cancer, and lung cancer [36, 48-50]. Based on previous studies of exosomes in NPC and our data indicating the clinical significance and characterization of NPC exosomes [51], we assumed that tumor-derived exosomes could directly induce T-cell tumor antigen-specific and non-specific immune dysfunction, resulting in tumor lymph node transfer and immune escape in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The level of circulating exosomes has also been reported to correlate with poor prognosis parameters and shorter survival in colorectal cancer patients [47]. Some exosomal proteins or miRNAs have shown prognostic value in cancer patients, for example, exosomal ΔNp73 and exosomal miRNA in colon cancer, breast cancer, and lung cancer [36, 48-50]. Based on previous studies of exosomes in NPC and our data indicating the clinical significance and characterization of NPC exosomes [51], we assumed that tumor-derived exosomes could directly induce T-cell tumor antigen-specific and non-specific immune dysfunction, resulting in tumor lymph node transfer and immune escape in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor (FGF), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF) [37, 38], and epidermal growth factor (EGF) [39] are what stand out most along with the mutated EGFR receptors [40, 41] and HGFR [42]. It has been proven that the exosomes deriving from both normal cells and cancer cells are mediators of the metastatic process as they can promote angiogenesis [43, 44], the invasion [45, 46], and proliferation of receptor cells to support the growth of the tumour [47, 48]. It has also been suggested that exosomes that derive from cancer because of their pleiotropic character could be involved in the development and progression of the tumour through the processes that enable the following: (a) tumour cells escaping from the immune system aid in launching the inflammatory response; (b) act on the differentiation of the fibroblasts and the mesenchymal cells; (c) improve the metastatic evolution of the tumour via the promotion of the epithelial/mesenchymal transition of the tumour cells and prepare the niches of the tumour cells for their new anatomical locations [49, 50].…”
Section: Metastatic Disseminationmentioning
confidence: 99%
“…For example, cancer cells release more exosomes than healthy ones. In consequence, it changes physiology of surrounding cells to have more favorable conditions for their metastasis (Grange et al, 2011; Soldevilla et al, 2013). Moreover, various miRNAs are detected in exosomes released from neurons and muscle cells (Forterre et al, 2013; Fruhbeis et al, 2013).…”
Section: Mirna At the Neuromuscular Junctionmentioning
confidence: 99%